Pemberdayaan Inovasi Kudapan Pencegahan Stunting: Egg Roll Ikan Lele Kelor Sebagai Kudapan Padat Gizi di Perumahan Graha Bumi Pertiwi RW 20, Desa Pepe, Kecamatan Sedati, Kabupaten Sidoarjo - Senja, Nabila; Azhari, Indah; Demarwan, Rizky Tri; Fakihardi, Fatan (Health Community Engagement, 2024)
Stunting remains a major public health issue in Indonesia, with a prevalence of 21.6% in 2022, exceeding the WHO standard (<20%). This condition affects children’s physical growth, cognitive abilities, and increases the risk of chronic disease. To support the national target of reducing the stunting rate to 14% by 2024, it is essential to implement affordable and nutritious food-based local dietary interventions. This Student Creativity Program (PKM) for Community Service aims to introduce an innovative local snack—catfish-moringa egg roll—as a nutrient-dense food to prevent stunting in Graha Bumi Pertiwi Housing RW 20, Pepe Village, Sedati Subdistrict, Sidoarjo Regency. The snack contains catfish (animal protein), tofu (plant-based protein), potatoes (carbohydrates), as well as moringa leaves and carrots (micronutrient-rich vegetables), providing 229.32 kcal and 16.63 grams of protein per 100 grams. The activities include education sessions for mothers of stunted toddlers, leaflet distribution, video presentations, and a cooking demonstration. This program is expected to increase maternal knowledge of nutritious food practices, improve children’s nutritional status, and reduce stunting in the targeted area. Moreover, it promotes the use of local food resources such as catfish to enhance the welfare of the community and local farmers. The outcomes of this program are anticipated to serve as a sustainable model for community-based nutritional interventions.